Housing Finance in Early 20th Century Suburban Toronto - Paterson, Ross (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1991)
This study examines the financing of housing production and consumption in five early twentieth-century Toronto suburbs. The study areas range in status from upper-middle class to working class.Research findings include the persistence of a traditional pattern of finance characterized by high levels of cash transactions and private financing. Institutional lenders, while influential in financing high-status housing played a relatively minor role in the overall provision of mortgage funding.The study adds to our understanding of the role of housing finance during this formative period when the major element of modern suburbanization, including the emergence of a corporate land development industry, were being established.